Values as an indicator of gender orientation - Cabrera, Aimelynn Marie D.
Understanding and learning the lives of human beings are truly interesting, may it about males, females, lesbians and gays. Even though only a small portion of their lives is being focused, one is still able to gather and learn important information. Results gathered may constitute as additional knowledge regarding these individuals. These will serve as a good contribution in understanding them more. Individuals constitute the society and it has been known that in a society certain norms are posed to serve as guide to persons' actions, behaviors and the total make-up of their daily lives. Some of these norms correspond to the values observed by people. Values are seen as important elements in shaping the views, actions and way of life of a certain person, although these may be affected by different factors within the society and the differences in experiences. Therefore, specific values are used in the study to help determine if the values of individuals specifically, males, females, lesbians and gays differ in their intensity or direction. Various factors within the society and the differences in experiences affect the values of a person, which contribute on how they may strongly or mildly adhere to a certain value. With this, one may determine if values can be an indicator of gender orientation. It is essential to look into things, which will advance the knowledge of individuals as to who they are amidst the structured format of a society.